Kegiatan Meningkatkan Pengalaman Pembelajaran Pendidikan Agama Kristen Melalui Kokurikuler dalam Pembacaan Alkitab - Endik Firmansah (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This research was motivated by the researcher's efforts as a Christian teacher to fill in the co-curricular activity of reading the Bible in schools, after the regulations for implementing full day school learning were issued. In this journal, the author discusses co-curricular activities to improve the learning experience of Christian religious education through reading the Bible. The research was conducted on Christian and Catholic students at SMP Negeri 2 Sei Menggaris who had taken part in Bible reading activities as a co-curricular activity. The research results show that co-curricular activities can improve students' learning experiences in Christian religious education. This activity can also increase students' interest in learning Christian religious education through Bible reading. In this activity, students are invited to read the Bible and discuss the meaning and meaning of the Bible text they read. Apart from that, this co-curricular activity can also help students to understand the teachings of the Christian religion in more depth through understanding the Bible texts they read. Therefore, the author recommends the use of co-curricular activities in learning Christian religious education as an effective and interesting method for students. ABSTRAKPenelitian ini dilatarbelakngi oleh usaha peneliti sebagai guru Agama Kristen untuk mengisi kegiatan kokurikuler membaca Alkitab di sekolah, setelah terbit peraturan untuk melaksanakan pembelajaran full day school.Dalam jurnal ini, penulis membahas tentang kegiatan kokurikuler untuk meningkatkan pengalaman pembelajaran pendidikan agama Kristen melalui pembacaan Alkitab. Penelitian dilakukan pada peserta didik beragama Kristen dan Katholik di SMP Negeri 2 Sei Menggaris yang telah mengikuti kegiatan membaca Alkitab sebagai kegiatan kokurikuler. Hasil penelitian menunjukkan bahwa kegiatan kokurikuler dapat meningkatkan pengalaman pembelajaran siswa dalam pendidikan agama Kristen. Kegiatan tersebut juga dapat meningkatkan minat siswa terhadap pembelajaran pendidikan agama Kristen melalui pembacaan Alkitab. Dalam kegiatan tersebut, siswa diajak untuk membaca Alkitab dan mendiskusikan arti dan makna dari teks Alkitab yang dibacanya. Selain itu, kegiatan kokurikuler ini juga dapat membantu siswa untuk memahami ajaran-ajaran agama Kristen secara lebih mendalam melalui pemahaman terhadap teks Alkitab yang dibaca. Oleh karena itu, penulis merekomendasikan penggunaan kegiatan kokurikuler dalam pembelajaran pendidikan agama Kristen sebagai metode yang efektif dan menarik bagi siswa. Kata-kata kunci: Manajemen Pendidikan, Pendidikan Agama Kristen, Kelompok Kokurikuler, Membaca Alkitab